Pathological & cytogenetic effects of different doses of Cobelt-60 in ‎induced chromosomal aberrations and sister-chromatid exchanges ‎‎– in rats - I.Al-Kaisie, Bushra. (The Iraqi Journal of Veterinary Medicine, 2005)
The present study was done in different period to study the pathological effects of different doses of Cobalt – 60 radiation which represent an example of gamma rays in white rats by study the pathological & cytogentic changes. Two groups of rats exposure ,first : C0 50 second C- 150 gray for (0,30,45,90)days and the 3rd group control .The results show significant increased P<0.01 in micronuclei with high dose (C-150). Chromosomal aberration and SCE showed significant P<0.01 increased mostly in C-150 at (45 7 90)days of exposure with frequency of breaks ,dicentric , acentric and ring shape with significant reduction in mitotic index (MI)and replicative (RI) index. Pathological changes revealed that increased and enlargement with granulomatous lesion of kidney , :Liver , lungs of (C-50) and (C-150)groups. Histopathological lesion showed development of adenocarcinoma in lung , liver with granulomatous lesion in